The Influence Phbs Counseling To Fulfillment Attitude Behavior Life Clean And Helathy SDN 1 Curug Student Regency Karawang In 2023 - Rinda Shinta Simaremare; Wintarsih; Dyah Mayasari Fatwah (Journal of Innovative and Creativity, 2025)
Behavior Life Clean And Healthy (PHBS) is practiced behavior by every individual at home household / family with awareness Alone as results learning For increase health . Besides that , PHBS too role active in realize healthy environment .  PHBS in schools is activity empowering students , teachers and public environment school For Want to do pattern life Healthy For create school Healthy . To know influence PHBS counseling in Fulfillment attitude And behavior student schoolgirl SDN 1 C urug In 2023 on 3rd grade elementary school . Study This is study quantitative with use design quasi experiment And approach one group pre- post test design . In design This before treatment given , moreover formerly sample given pretest ( test beginning ) and after treatment sample given posttest ( test end ). Design This used in accordance with the goal will be achieved that is For know influence PHBS counseling on student attitudes . analysis use Wilcoxon test was obtained mark P = <.001 <0.005 so can concluded there is influence PHBS counseling towards fulfillment attitude behavior life clean And Healthy students of SDN 1 Curug Regency Karawang . There is influence PHBS counseling towards fulfillment attitude behavior life clean And Healthy students of SDN 1 Curug Regency Karawang and Expected can used as material reference For student schoolgirl in do behavior clean life And healthy in the environment his school And life daily